If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -2)(x + 3)(3x + 5) = 0 Reorder the terms: (-2 + x)(x + 3)(3x + 5) = 0 Reorder the terms: (-2 + x)(3 + x)(3x + 5) = 0 Reorder the terms: (-2 + x)(3 + x)(5 + 3x) = 0 Multiply (-2 + x) * (3 + x) (-2(3 + x) + x(3 + x))(5 + 3x) = 0 ((3 * -2 + x * -2) + x(3 + x))(5 + 3x) = 0 ((-6 + -2x) + x(3 + x))(5 + 3x) = 0 (-6 + -2x + (3 * x + x * x))(5 + 3x) = 0 (-6 + -2x + (3x + x2))(5 + 3x) = 0 Combine like terms: -2x + 3x = 1x (-6 + 1x + x2)(5 + 3x) = 0 Multiply (-6 + 1x + x2) * (5 + 3x) (-6(5 + 3x) + 1x * (5 + 3x) + x2(5 + 3x)) = 0 ((5 * -6 + 3x * -6) + 1x * (5 + 3x) + x2(5 + 3x)) = 0 ((-30 + -18x) + 1x * (5 + 3x) + x2(5 + 3x)) = 0 (-30 + -18x + (5 * 1x + 3x * 1x) + x2(5 + 3x)) = 0 (-30 + -18x + (5x + 3x2) + x2(5 + 3x)) = 0 (-30 + -18x + 5x + 3x2 + (5 * x2 + 3x * x2)) = 0 (-30 + -18x + 5x + 3x2 + (5x2 + 3x3)) = 0 Combine like terms: -18x + 5x = -13x (-30 + -13x + 3x2 + 5x2 + 3x3) = 0 Combine like terms: 3x2 + 5x2 = 8x2 (-30 + -13x + 8x2 + 3x3) = 0 Solving -30 + -13x + 8x2 + 3x3 = 0 Solving for variable 'x'. The solution to this equation could not be determined.
| 2c+5-25.5c=-25.5 | | 7m+4=3 | | 3(x-4)=2+x | | 3x+2+x+4=18 | | y=Asinx | | -4.5(3n-5)=26.5+8n | | w^2+2w=-10+6k-k^2 | | 4a(a-3)=0 | | -3+3.5(1-8.5v)=16.5 | | 5(r+1)-[2(3-2r)-3(3-r)]=2(r+5)-4 | | 6/z=42/49 | | 5a+3(a-1)=2 | | -4x^2+24k-36=0 | | 7a+5b+3a-2b= | | Y-5=Y-12 | | 10-2n=22 | | 12.x/9=8/36 | | 12.j/9=8/36 | | 2y^2+xy=14 | | 25+20x=15+22x | | 3/8=c/40 | | 78-38-x=24 | | Mover-15=-4 | | 6/x=42/49 | | (Xy^2+y-x)dx+x(xy+1)dy=0 | | 3x+2[-3(x+2)]=2x | | n+25=80 | | 10-n=-90 | | 2y-1/2=2/3 | | z^2(2+7i)z+(-11+7i)=0 | | 8x+25=3x+15 | | -21+15x=6y |